“Transformative dynamics of the gig economy: Technological impacts, worker well-being and global research trends” - Rachoru Himani Srihita; Gurunadham Goli; Rajyalaxmi M; R Gobinath (International Journal of Engineering Business Management)
Digital platforms play a vital role in shaping today’s labour market, enabling temporary hires and freelance employment in the gig economy. This on-demand, digital economy spans various professions and remote work opportunities. Technological advancements have significantly evolved gig work since the industrial age, improving work-life balance and psychological well-being. Using the Scopus database, a literature analysis on the gig economy was conducted with 1624 documents narrowed to 549 documents based on subject area, document type, publication stage, keywords, and language and examining social, economic and technological factors. This study highlights the evolving nature of non-traditional, online-platform- driven employment through which author’s explored the gig economy, its challenges, ethical issues, and career development and workers experiences. The analysis used R Studio Software to visualize keyword themes using a strategic thematic map, which signifies the structure and development of themes within the gig economy. This study used Origin Pro for author analysis which found GRAHAM as the top author. VOS Viewer for bibliographic coupling which identified USA and UK as top collaborating countries and also highlight the eight clusters of keyword analysis. For sustainable growth, further research should explore the platform economy, gig employment, and worker well-being, assessing technological innovations to create adaptable job opportunities. This will help the gig economy to accommodate market dynamics and ensure diverse and stable employment across various sectors.